The Case for an Expanded Concept of Trained Immunity - Antonio Cassone (American Society for Microbiology, 2018)
ABSTRACT Trained immunity was originally proposed as a program of innate immunity memory by innate immunity cells of hematopoietic origin such as the monocytes/macrophages and the NK cells. Here I discuss some old and new data justifying this program and some specific, still unanswered, questions it raises regarding the model fungus Candida albicans and the chronic, inflammatory vulvovaginal disease it causes. Building upon this well-established program, the recent reports that epithelial cells of mammals can also acquire memory from previous stimulations, and the apparent intrinsic ability of many living cells from bacteria to mammals to learn from experience, I suggest an expansion of the concept of trained immunity to include all cells of different lineages with the potential of memorizing previous microbial encounters. This expansion would better fit the complexity of innate immunity and the role it plays in infectious and inflammatory diseases.